Beta of Viet Nam Stock Investment Industry Under Leverage Impact During and After The Global Crisis 2007-2011 - Huy, Dinh Tran Ngoc (IJRDO - Journal of Business Management, 2019)
This paper estimates the impacts of external financing on market risk for the listed firms in the Viet nam non-banking stock investment industry, esp. after the financial crisis 2007-2009. First, by using quantitative and analytical methods to estimate asset and equity beta of total 10 listed companies in Viet Nam non-banking stock investment industry with a proper traditional model, we found out that the beta values, in general, for many institutions are acceptable. Second, under 3 different scenarios of changing leverage (in 2011 financial reports, 30% up and 20% down), we recognized that the risk level, measured by equity and asset beta mean, decreases when leverage increases to 30% and vice versa. Third, by changing leverage in 3 scenarios, we recognized the dispersion of risk level increases (measured by equity beta var) if the leverage increases up to 30%. Finally, this paper provides some outcomes that could provide companies and government more evidence in establishing their policies in governance.